PENGARUH BEBAN KERJA DAN BURNOUT TERHADAP TURNOVER INTENTION - Anggi Saputra; Meiffa Herfianti; Merta Kusuma (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to analyze the influence of workload and burnout on employee turnover intention at PT. Sinar Niaga Sejahtera Bengkulu. This research uses a quantitative approach with a survey method, where data is obtained through distributing questionnaires to employees of PT. Sinar Niaga Sejahtera Bengkulu. Data analysis techniques used include validity test, reliability test, multiple linear regression test, t-test, and F-test with the help of statistical software. The results showed that partially workload has a positive and significant effect on employee turnover intention, as evidenced by a significance value of 0.000 < 0.05 and t-value greater than t-table. Burnout also has a positive and significant effect on employee turnover intention with a significance value of 0.002 < 0.05 and t-value > t-table. Furthermore, simultaneously workload and burnout have a significant effect on employee turnover intention, as indicated by F-value > F-table and a significance value of 0.000 < 0.05. The findings of this study indicate that an unbalanced workload and high burnout can increase employee intention to leave the organization. Therefore, based on the results of the study, it can be concluded that workload management and burnout prevention contribute to reducing employee turnover intention at PT. Sinar Niaga Sejahtera Bengkulu. Keywords: Workload, Burnout, Turnover Intention